2001
DOI: 10.1161/01.hyp.37.3.856
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Cardiac Effects of Salt With Fludrocortisone in Hypertension

Abstract: Abstract-The effect of salt on blood pressure (BP) is controversial. A more important question is whether salt can produce cardiac target-organ damage, irrespective of its effect on BP. We assessed the effect of salt with fludrocortisone on QT dispersion and echocardiographic left ventricular diastolic function in a prospective interventional study involving 29 hypertensive subjects with a raised aldosterone/renin ratio who were hospitalized for investigation of possible primary aldosteronism. Each subject ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…11 Although the magnitude of rise in QT dispersion in the present study was smaller, an effect was still seen in normal healthy young adults. The mechanism for this effect of salt is unclear.…”
Section: Oral Salt Loading and Qt Dispersioncontrasting
confidence: 61%
See 2 more Smart Citations
“…11 Although the magnitude of rise in QT dispersion in the present study was smaller, an effect was still seen in normal healthy young adults. The mechanism for this effect of salt is unclear.…”
Section: Oral Salt Loading and Qt Dispersioncontrasting
confidence: 61%
“…10 We have previously reported that in hypertensive subjects with increased aldosterone activity, salt loading not only impairs left ventricular diastolic function, but also increases QT dispersion, a measure of cardiac electric depolarization. 11 One study has previously examined the effect of sodium loading on vascular endothelium in 7 normal subjects and found no significant effect on endothelial-dependent vasodilation. 12 However, our prior experience prompted us to repeat this with a larger study group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Li et al, 16 in a large-scale, blinded randomized trial in rural China, confi rmed that a potassium chloride-containing salt substitute is an effective and acceptable means of blood pressure control. Although our calculated method of salt intake was not precise, results from our analysis also indicated that higher salt intake contributed to the progression of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium salt is one of the most important environmental factors for hypertension. In this study, QTd was reduced in normotensives after low-salt diet while increased after high-salt diet intervention, suggesting the correlation between salt intake and QTd Lim et al [14]. Reported that QTd had been increased in hypertensive patients after salt loading, while Tzemos et al [9] further observed that QTd had also been increased in normotensive youngs after salt loading.…”
Section: Discussionmentioning
confidence: 47%